2007
DOI: 10.1088/0957-4484/18/31/315601
|View full text |Cite
|
Sign up to set email alerts
|

Core/shell fluorescent magnetic silica-coated composite nanoparticles for bioconjugation

Abstract: A new class of highly fluorescent, photostable, and magnetic core/shell nanoparticles has been synthesized from a reverse microemulsion method. The obtained bifunctional nanocomposites were characterized by transmission electron microscopy (TEM), ultraviolet–visible (UV–vis) spectrometry, photoluminescence (PL) spectrometry, and fluorescence microscopy in a magnetic field. To further improve their biocompatibility, the silica-coated nanoparticles were functionalized with amino groups. The fluorescent magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 24 publications
(43 reference statements)
1
80
0
2
Order By: Relevance
“…14,41 In this work we have described the synthesis of well-defined core/shell nanoparticles comprising a core of lanthanopolyoxotunsgstates encapsulated by silica shells, which in principle can be further exploited as alternative bio-labels. The visible photoluminescence of the POM/SiO 2 systems can be tuned by modifying the coordination sphere of the lanthanopolyoxometalate and/or its chemical composition.…”
Section: Discussionmentioning
confidence: 99%
“…14,41 In this work we have described the synthesis of well-defined core/shell nanoparticles comprising a core of lanthanopolyoxotunsgstates encapsulated by silica shells, which in principle can be further exploited as alternative bio-labels. The visible photoluminescence of the POM/SiO 2 systems can be tuned by modifying the coordination sphere of the lanthanopolyoxometalate and/or its chemical composition.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that the magnetic core can be replaced by semiconductor quantum dots or fluorescence molecules doped into the silica shell to form fluorescent core/shell silica nanoparticles. [9][10][11] These silica-coated fluorescent magnetic nanoprobes enabled development of biomedical platforms for simultaneous imaging, diagnosis, and therapy. [12][13][14] However, it is still a challenge to fabricate fluorescent magnetic nanoprobes with high photostability, high payloads of dye, and desirable outer surfaces for further modification with functional or target moieties.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation and characterization of FMNPs were reported in our previous papers. [25][26][27] The iPS cells were seeded on the cover slips and treated with growth medium containing FMNPs (50 µg/mL) for 4 hours at 37°C with 5% CO 2 . Afterwards, the cells were rinsed with PBS and fixed with 2.5% glutaraldehyde for 30 minutes.…”
Section: Labeling Ips Cells With Fmnpsmentioning
confidence: 99%